Mineralization Related to Post-Acadian Tectonism in Southern New Brunswick - Ruitenberg, A.; McCutcheon, S.; Venugopal, D.; Pierce, G. (Geoscience Canada, 1977)
Summary The formation of post-Acadian mineral deposits in southern New Brunswick is correlated with a distinct sequence of tectonic events. A great variety of epigenetic deposits occur within and along the contacts of Middle Devonian to Early Carboniferous igneous intrusions and associated sub-volcanic stocks, that were emplaced in a succession of distensional structures. The host rocks of the stratiform deposits generally reflect formation contemporaneous with gentle epeirogenic movements. The intervening strata reflect episodes of intense faulting and folding. Climatic conditions associated with the formation of different stratiform deposits varied from arid to humid.